2003
DOI: 10.1007/s11746-003-0774-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative properties and enzymatic synthesis of ascorbyl FA esters

Abstract: Efficient synthesis of unsaturated FA esters of ascorbic acid is possible with only a small excess of one of the reactants in t-amyl alcohol using Candida antarctica lipase as biocatalyst. Using free acids, we obtained yields that were comparable to yields reached using vinyl-activated acyl donors (71, 80, and 86% yields of esters with FA excesses of 1:1, 1:1.5, and 1:2, respectively). As very low water activity is needed to achieve sufficiently high yields of product, molecular sieves were used to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 12 publications
(10 reference statements)
6
40
1
4
Order By: Relevance
“…the highest initial rates were accomplished at 60 , and maximum ascorbyl oleate concentration was achieved at 55 16 . In a two separated investigations of ascorbyl palmitate synthesis using same lipase preparation as in our study high yields were reported at 55 10 and 60 13 . Interestingly, in optimization study using same lipase preparation in synthesis of ascorbyl laurate temperature optimum as 3.2 The effect of molecular sieves addition on specific product yield Since water is product of esterification, the optimization of initial water concentration is not sufficient to provide high reaction yields.…”
Section: Optimization Of Lipase-catalyzed Synthesis Of Ascorbyl Oleatesupporting
confidence: 59%
See 3 more Smart Citations
“…the highest initial rates were accomplished at 60 , and maximum ascorbyl oleate concentration was achieved at 55 16 . In a two separated investigations of ascorbyl palmitate synthesis using same lipase preparation as in our study high yields were reported at 55 10 and 60 13 . Interestingly, in optimization study using same lipase preparation in synthesis of ascorbyl laurate temperature optimum as 3.2 The effect of molecular sieves addition on specific product yield Since water is product of esterification, the optimization of initial water concentration is not sufficient to provide high reaction yields.…”
Section: Optimization Of Lipase-catalyzed Synthesis Of Ascorbyl Oleatesupporting
confidence: 59%
“…Generally, lipases capable of ascorbyl ester synthesis are very rare, hence enzyme preparation used in our study Novozyme ® 435 was used in majority of reported studies 2,10,12,13,24 so comparison with results is simple. Applied enzyme concentrations were usually high, up to 2 w/v .…”
Section: Enzyme Loading Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the steadily growing demand for natural materials, the synthesis of esters of ascorbic acid by lipasecatalyzed reactions has become of current commercial interest to be used as an antioxidant in the food, cosmetic and pharmaceutical industries (Viklund et al, 2003).…”
Section: Introductionmentioning
confidence: 99%